Science! - Beall, Abigail; Bull, Peter, 1960-; Carter, Stuart; Challoner, Jack.; Dingle, Adrian, 1967-; Harding, Jason (Digital artist) (New York, N.Y. : DK Penguin Random House, 2018)
"Discusses key concepts in biology, physics, chemistry, and other scientific fields, and includes fast fact boxes, images and diagrams, and information about key scientists and their work"--From publisher.
"At" in statement of responsibility represented by at symbol.
Includes index.
8.0
5-8.
5-8
Keywords: Science -- Juvenile literature; Science; Science